PERSEPSI GURU KELAS TERHADAP KARAKTER ABK DALAM PENGIMPLEMENTASIAN KURIKULUM 2013 - Abidinsyah Abidinsyah (Program Studi PGSD STKIP PGRI Banjarmasin, 2021)
Inclusion education is an educational system that provides opportunities to all children who have disabilities and have the potential of intelligence or special talents to follow learning in an educational environment together with students in general. The implementation of the 2013 curriculum in education emphasizes character education. Teachers certainly have difficulty in internalizing character values in ABK, considering that not all characters can be internalized to students. In this case, teachers have different perceptions in internalizing character values in this 2013 curriculum. This study aims to describe the perception of classroom teachers towards: School and teacher readiness, learning process, and various obstacles that occur in internalizing the values of abk character in the 2013 curriculum at SDN Banua Anyar 4 Banjarmasin. This type of research is qualitative descriptive research. Data collection techniques are conducted through observation and interview. The results of the study were obtained as follows: (1) Classroom teachers have the same perception of the readiness of schools and teachers in internalizing character values in abk, namely schools making policies, developing programs that support the process of internalizing character values, and schools providing special guidance teachers, and providing adequate facilities. While the readiness of teachers in internalizing character values in ABK is a learning tool in accordance with the provisions of the 2013 curriculum, learning media, teaching materials, and attitude assessment instruments, (2) Class teachers have the same perception of the character of ABK in the learning process, according to the teachers of abk class has different characters in accordance with annoyance or obstacles suffered by ABK. While internalizing the character value in abk in the learning process, there are three stages, namely the planning stage, implementation stage, and evaluation stage, (3) The class teacher has difficulty in the lack of involvement of parents in internalizing character values, the difficulty of internalizing the value of discipline character, and the limitation of teacher knowledge in ABK.